Art Education in a Transitional Moment: Bridging Academic Theory and Field Practices, Reflecting on Two Decades and Envisioning the Future - Viens, Marie-Pier; LeRue, David (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
This article examines the evolution of art education in Canada over the past two decades, highlighting the shift from skills-based approaches to broader methodologies centered on “arts-thinking,” integrating visual culture, social justice, and research-creation. Despite these theoretical advancements, the authors observe a disconnect between academic discourse and practical application in schools and communities. To bridge this gap, art educators Marie-Pier Viens and David LeRue share their experiences integrating theory and practice in their respective teaching contexts. Viens discusses collaborative project-based learning in secondary schools, in connection with community artists, emphasizing the development of essential skills and engagement with contemporary issues through art. LeRue explores community-based art education, addressing its potential for fostering arts-thinking among diverse populations outside traditional academic settings. The authors propose closer ties between theory and practice to provide learners with critical thinking skills necessary to engage in contemporary artistic discourse.